FORMER ICE SHEET BASED ON THE NEWLY OBSERVED GLACIAL LANDFORMS AND ERRATICS IN THE CENTRAL SØR RONDANE MOUNTAINS, EAST ANTARCTICA - ヒラカワ, カズオミ; モリワキ, キイチ; HIRAKAWA, Kazuomi; MORIWAKI, Kiichi (National Institute of Polar Research, 1990)
P(論文) Reconstruction of the former ice sheet extent was revised on the basis of newly observed glacial landforms and erratics in the central Sør Rondanc Mountains. Roches moutonnees on the summit of southern Lunckeryggen and crratics on the flat summit surface of west Brattnipene are in particular significant to revise the reconstruction of the former ice sheet and its longitudinal profile. Central Sør Rondane Mountains were mostly overridden by the ice sheet, except several small nunataks. Roches moutonnees and ice-smoothed mountain slope in the summit area of southern Lunckeryggen attaining to 1000m or more above the present outlet glacier surface are evidence of the northward advance of ice fall, ca. 10km, where ice generally at least 400m thicker than at present. departmental bulletin paper